2007
DOI: 10.1080/10615800701695131
|View full text |Cite
|
Sign up to set email alerts
|

Stress processes in HIV-positive African American mothers: Moderating effects of drug abuse history

Abstract: This study examined the mechanism by which stressors, dissatisfaction with family, perceived control, social support, and coping were related to psychological distress in a sample of HIV-positive African American mothers. Additional analyses explored whether women who had a history of a drug abuse or dependence diagnosis differed either on levels of the study variables or the model pathways. The results indicated that HIV-positive African American mothers who had higher levels of stressors perceived their stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…[12][13][14][15] Discrimination at schools, work places and humiliation is very common in most of the places across the world. [16][17][18][19][20][21] In this study the positive network has given the suffering woman, knowledge, hope and support. A study conducted by Michael Robbins also gives similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Discrimination at schools, work places and humiliation is very common in most of the places across the world. [16][17][18][19][20][21] In this study the positive network has given the suffering woman, knowledge, hope and support. A study conducted by Michael Robbins also gives similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, its contribution to the medium predictive relationship assessed in this regression analysis is minimal. In contrast, multiple studies in the research literature found relationships between poor health behaviors among HIVinfected pregnant women and either a history of substance use, a substance abuse diagnosis, or an active substance use problem (Burns et al, 2008;Mellins et al, 2003;Napravick et al, 2000). Do variables measuring risks for poor maternal health behaviors, such as history of substance use diminish when examined in conjunction with potential protective factors against adversity or facilitators of wellbeing?…”
Section: Associations Between Maternal-fetal Attachment and Health Bementioning
confidence: 86%
“…Mothers with history of drug use diagnosis, compared to those without this history, reported stronger effect of avoidant coping on psychological distress, and employed larger support networks as a means of coping (Burns et al, 2008). However, women with a history of drug abuse did not benefit as much from the increased social support, as did those without this history (Burns et al, 2008). Mellins et al (2002) found that a diagnosis of psychiatric or substance abuse disorders and parenting stress strongly correlated with ART non-adherence in a cohort of HIV-infected mothers living in a U.S.…”
Section: Maternal Health Behaviors Among Pregnant Women With Hiv/aidsmentioning
confidence: 99%
See 2 more Smart Citations